Individualized clinical management of patients at risk for Alzheimer's dementia. Issue 12 (30th October 2019) - Isaacson, Richard S.; Hristov, Hollie; Saif, Nabeel; Hackett, Katherine; Hendrix, Suzanne; Melendez, Juan; Safdieh, Joseph; Fink, Matthew; Thambisetty, Madhav; Sadek, George; Bellara, Sonia; Lee, Paige; et al.
Abstract: Introduction: Multidomain intervention for Alzheimer's disease (AD) risk reduction is an emerging therapeutic paradigm. Methods: Patients were prescribed individually tailored interventions (education/pharmacologic/nonpharmacologic) and rated on compliance. Normal cognition/subjective cognitive decline/preclinical AD was classified as Prevention. Mild cognitive impairment due to AD/mild‐AD was classified as Early Treatment. Change from baseline to 18 months on the modified Alzheimer's Prevention Cognitive Composite (primary outcome) was compared against matched historical control cohorts. Cognitive aging composite (CogAging), AD/cardiovascular risk scales, and serum biomarkers were secondary outcomes. Results: One hundred seventy‐four were assigned interventions (age 25–86). Higher‐compliance Prevention improved more than both historical cohorts ( P = .0012, P < .0001). Lower‐compliance Prevention also improved more than both historical cohorts ( P = .0088, P < .0055). Higher‐compliance Early Treatment improved more than lower compliance ( P = .0007). Higher‐compliance Early Treatment improved more than historical cohorts ( P < .0001, P = .0428). Lower‐compliance Early Treatment did not differ ( P = .9820, P = .1115). Similar effects occurred for CogAging. AD/cardiovascular risk scales and serum biomarkers improved. Discussion: Individualized multidomain interventions may improve cognition and reduce AD/cardiovascular risk scores in patients at‐risk for AD dementia.